On certain ‘tools’for research into the perception and creation of music and the complex ways in which they affect one another - Humięcka-Jakubowska, Justyna (Interdisciplinary Studies in Musicology, 2018)
Perception is a constructive mental process, which cannot be considered impersonally. Similarly, music cannot be cognised solely on the basis of its score, since its coming into being is strictly connected to the activation of human memory and sound imagination. The patterns that emerge from the sounds of heard music enable the listener to draw conclusions regarding the structures those sounds embody. However, such conclusions are accompanied by a degree of uncertainty, which concerns not just the perceived moment of the heard music, but also the way in which it is represented in the listener’s memory. Perception is an inferential, multi-layered, uncertain process, in which particular patterns seem more likely than others. Mental representations of those probabilities lie behind such essential musical phenomena as surprise, tension, expectation and pitch identification, which are fixed elements of the perception of music. The aim of the present article is to describe the essence of three selected types of music modelling, based on spectral anticipation (Shlomo Dubnov), based on memory (Rens Bod), and exploiting the dynamic character of music to obtain information (Samer Abdallah and Mark Plumbley). All these models take account of the element of uncertainty that accompanies the perception of music; hence they make use the foundations of information theory and statistical analysis as measurement ‘tools’. The use of these tools makes it possible to obtain numerical rates, which inform us of the degree of predictability of the musical structures being analysed. One crucial advantage of these methods is the possibility of evaluating them in respect to the use of real musical structures, deriving from actual music, and not abstract structures formed for the purposes of research. We obtain cognitive insight into the analysed music by employing methods of a mathematical provenance, and so we have the possibility of examining music whilst taking account of the role of the listener, but with the use of objectivised methods.